Association of serum surfactant protein D and SFTPD gene variants with asthma in Danish children, adolescents, and young adults. Issue 2 (15th November 2021) - Hoffmann‐Petersen, Benjamin; Suffolk, Raymond; Petersen, Jens J. H.; Petersen, Thomas H.; Brasch‐Andersen, Charlotte; Høst, Arne; Halken, Susanne; Sorensen, Grith L.; Agertoft, Lone
Abstract: Background: Surfactant Protein D (SP‐D) is a pattern recognition molecule belonging to the family of collectins expressed in multiple human organ systems, including the lungs. Previous studies have shown that SP‐D levels in bronchoalveolar lavage samples decrease and serum levels increase in patients suffering from asthma, possibly due to a combination of induced SP‐D synthesis and decreased air–blood barrier integrity. The aims of this study were to investigate whether serum levels of SP‐D and common variants in the SP‐D gene were associated with asthma in adolescents and young adults. Methods: Prospective observational study including 449 adolescents and young adults (age 11–27 years) previously diagnosed with asthma during a 2‐year period from 2003 to 2005 (0–16 years). At follow‐up from 2016 to 2017, 314 healthy controls with no history of asthma were recruited. Serum SP‐D was analyzed on samples obtained at baseline as well as samples obtained at follow‐up. SP‐D genotyping was performed for rs721917, rs2243639, and rs3088308. Results: No differences were found in mean levels of sSP‐D and SFTPD genotype among subjects with current asthma, no current asthma, and controls . Serum SP‐D and SFTPD genotype were not associated with any clinical parameters of asthma. Furthermore, baseline sSP‐D was not associated with asthma at follow‐up. Conclusion: Serum surfactant protein D and common SP‐D gene variants were not associated with asthma in Danish adolescents and young adults with mild to moderate asthma. Serum surfactant protein D did not demonstrate any value as a clinical biomarker of asthma. Abstract :